Antiviral activities of Artemisia vulgaris L. extract against herpes simplex virus - Ji Xiao; Ping Liu; Yuze Hu; Tao Liu; Yuying Guo; Pinghua Sun; Junxia Zheng; Zhe Ren; Yifei Wang (BMC, 2023)
Abstract Background Artemisia vulgaris L. is often used as a traditional Chinese medicine with the same origin of medicine and food. Its active ingredient in leaves have multiple biological functions such as anti-inflammatory, antibacterial and insecticidal, anti-tumor, antioxidant and immune regulation, etc. It is confirmed that folium Artemisiae argyi has obvious anti-HBV activity, however, its antiviral activity and mechanism against herpesvirus or other viruses are not clear. Hence, we aimed to screen the crude extracts (Fr.8.3) isolated and extracted from folium A. argyi to explore the anti-herpesvirus activity and mechanism. Methods The antiherpes virus activity of Fr.8.3 was mainly characterized by cytopathic effects, real-time PCR detection of viral gene replication and expression levels, western blotting, viral titer determination and plaque reduction experiments. The main components of Fr.8.3 were identified by using LC-MS, and selected protein targets of these components were investigated through molecular docking. Results We collected and isolated a variety of A. vulgaris L. samples from Tangyin County, Henan Province and then screened the A. vulgaris L. leaf extracts for anti-HSV-1 activity. The results of the plaque reduction test showed that the crude extract of A. vulgaris L.-Fr.8.3 had anti-HSV-1 activity, and we further verified the anti-HSV-1 activity of Fr.8.3 at the DNA, RNA and protein levels. Moreover, we found that Fr.8.3 also had a broad spectrum of antiviral activity. Finally, we explored its anti-HSV-1 mechanism, and the results showed that Fr.8.3 exerted an anti-HSV-1 effect by acting directly on the virus itself. Then, the extracts were screened on HSV-1 surface glycoproteins and host cell surface receptors for potential binding ability by molecular docking, which further verified the phenotypic results. LC-MS analysis showed that 1 and 2 were the two main components of the extracts. Docking analysis suggested that compounds from extract 1 might similarly cover the binding domain between the virus and the host cells, thus interfering with virus adhesion to cell receptors, which provides new ideas and insights for clinical drug development for herpes simplex virus type 1. Conclusion We found that Fr.8.3 has anti-herpesvirus and anti-rotavirus effects. The main 12 components in Fr.8.3 were analyzed by LC-MS, and the protein targets were finally predicted through molecular docking, which showed that alkaloids may play a major role in antiviral activity.